A partial tumor irradiation approach for complex bulky disease - Tubin, Slavisa (Seminars in radiation oncology, 2024)
A large proportion of cancer patients present with unresectable bulky disease at baseline or following treatment failure. The data available in the literature suggest that the vast majority of these patients do not benefit from available standard therapies. Therefore the clinical outcomes are poor; patients are desperate and usually relegated to palliative or best supportive care as the only options. Large tumor masses are usually hypoxic, resistant to radiation and systemic therapy, with extensive regional infiltration of the surrounding critical organs, the presence of which makes it impossible to deliver a radical dose of radiation. Promising data in terms of improved therapeutic ratio where such complex tumors are concerned can be seen with the use of new emerging unconventional radiotherapy techniques known as spatially fractionated radiotherapies (SFRT). One of them is PATHY, or PArtial Tumor irradiation targeting HYpoxic segment, which is characterized by a very short treatment course offering a large spectrum of therapeutic benefits in terms of the symptom relief, quality of life, local tumor control, neoadjuvant and immunomodulatory effects.